Proceeding of The 4th International Seminar on Linguistics (ISOL-4). Language in Disruptive Technology - S.S, Handoko (De Gruyter, 2019)
Description The rapid development of technology has led to a borderless community which may affect social life, including language. Through the disruptive technology of the era, the issue of language use and how technology affects language has arisen as a critical aspect of human communication. The current ISOL-4 tries to bring the issues of Language and Disruptive Technology to academic discussion. Aims and Scope LANGUAGE AND TECHNOLOGY Language and media, Natural Language Processing, Language and Artificial Intelligence, Corpus Linguistics, Language Education and Technology, Speech and Language Therapy, Language and Cyber Threat, and Related Issues. LANGUAGE AND SOCIAL CHANGE Language and Global Development, Language and Politics, Language and Gender, Language and Conflict, Language and Disaster Management LANGUAGE AND CULTURE Language and Identity, Cross Cultural Communication, Language Preservation RELATED STUDIES Reasearch related to language and technology from various fields Instructions for Authors As an author, it is crucial to follow the guidelines and formatting instructions to prepare and submit your paper in order to have it published in proceedings. Before submitting the paper, please use the conference template which can be found in the the website: http://isol.fib.unand.ac.id/ Each individual is limited to one personal appearance on the programme as a presenting author. This policy precludes acceptance of papers for more than one presentation. In other words, an author can submit and present only one paper. However, a presenter can always be a non-presenting co-author on additional papers. Please read the instructions carefully prior to submitting: Each paper can only be submitted to ONE track. Submitted pap